PENGARUH TERAPI BERMAIN PUZZLE TERHADAP TINGKAT KECEMASAN HOSPITALISASI PADA ANAK USIA PRA SEKOLAH (3-6 TAHUN) DI RSUD DR. HARJONO KABUPATEN PONOROGO - Hariyadi Hariyadi (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
From the data obtained shows the number of children treated more is pre-school age than other ages. In Harjono Regional Hospital, Ponorogo Regency shows that almost all children treated experience anxiety. Playgrounds are already available, but for play facilities it is still lacking and play therapy has not been done. The research design used in this study was experimental research design. The population of this study was patients of preschool children who were cared for in the children's room of RSUD Harjono, Ponorogo Regency. This study used a sampling technique with purposive sampling to obtain 19 respondents. Data analysis used was descriptive analysis and Wilcoxon test. The results show that before puzzel therapy from 19 respondents who experience moderate levels of anxiety were 14 respondents (73.7%). Whereas after exercising from 19 respondents who experience anxiety levels were 4 respondents (21.1%). Statistical results with the Wilcoxon test with 95% significance level obtained P-value of 0.000 (p